Sublaminar stabilization (stapling) of the caudal cervical instability in Yorkshire terrier—A case report - Sterna, Jacek; Degórska, Beata; Bonecka, Joanna; Baranski, Mikhal (Frontiers in Veterinary Science, 2025)
This case report describes the long-term outcome of surgical treatment of rare spinal instability in small-breed dogs. A 2-year and 7-month-old male Yorkshire terrier, weighing 1.5 kg, was presented with tetraparesis and proprioceptive deficits, neck pain, and intact deep pain sensation for a clinical examination. The conservative treatment had been unsuccessful for 20 months. A diagnosis of C6-C7 instability with a slight vertebral subluxation was made, which led to the decision about sublaminar stabilization. The Kirschner wire was placed on both sides of the spinous processes from C5 to T1 using the left dorsal approach. A polyamide monofilament suture was passed under the laminas of the cervical fifth, sixth, and seventh vertebras and tied around the Kirschner wire. The cranial end of the Kirschner wire had been stuck under the lamina of the fourth cervical vertebra after the surgery. A reoperation was performed 33 days later. The cranial end of the Kirschner wire was removed from under the lamina and bent dorsally. The dog was ambulatory and without neck pain 2 days after the reoperation. Five years after the surgical treatment, the dog is still ambulatory with normal proprioceptive positioning but with subtle ataxia. This kind of stapling sublaminar stabilization may be a useful method as a primary means for stabilization in cases of cervical spine instability in small dogs. It may also serve as a secondary procedure in cases of severe complications after the failure of other methods applied from the ventral approach.